TEMPERATURE DIVERSIFICATION OF THE SURFACE LAYER OF WATER IN THE KARST LAKES IN THE STASZÓW REGION (NIDZIAŃSKA BASIN) - ZIELIŃSKI, ARTUR (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2021)
The north-eastern part of Nidziańska Basin, near Staszów, boasts a large grouping of small but relatively deep lakes of karst origin. In 2010, 26 of them underwent regular measurements of the temperature of their surface layer of water. The results show that although the basins are situated close to each other and the area has similar characteristics, the temperature differs significantly. The thermal differences reach 11.6ºC. The warmest lakes appear to be Lake Łajba, Duży Staw, Lakes Torfowe I and Torfowe II. However, the coldest surface water is in lakes Piąty Staw, a small unnamed lake located near Lake Ciemne and an unnamed lake sandwiched between Lake Szyja and Lake Jasne. The fact that the temperature of the water goes up results directly from solar radiation, which was the strongest in the case of Lake Łajba, located in an open area. However, the coldest basins were located in the central parts of the lakes of the floating peat islands. Those biogenic islands are perfect “insulators”, protecting the water from thermal radiation. Moreover, the lakes which are fed with soligenous water supplies, tend to have a lower temperature.